Artificial neural network to estimate an index of water quality - Quiñones Huatangari, Lenin; Ochoa Toledo, Luis; Kemper Valverde, Nicolás; Gamarra Torres, Oscar; Bazán Correa, José; Delgado Soto, Jorge (Enfoque UTE, 2020)
The artificial neural network (RNA) is a computational model that emulates the biological neural system in information processing. The originating models are suitable for the purpose of describing long-term specifics, in addition to nonlinear relationships. This tool is used to predict physical chemical and microbiological parameters that influence water quality. The United States National Sanitation Foundation proposed a water quality index, known as the NSF WQI. This article describes the design, training and use of the three-layer neural perceptron neural model for the calculation of the NSF WQI of the Utcubamba River and its tributaries. Using the Matlab software and applying the Levenberg-Marquardt training algorithm, the optimal RNA architecture was found to be 6-12-1, plus the percentage for the training, validation, and test sets of 70 %, 10 %, and 20 % respectively. RNA performance has been evaluated using the root of the root mean square error (RMSE) and the correlation coefficient (R). High correlations (greater than 0.94) were made between the measured and predicted values. Finally, the RNA proposal offers a useful alternative for the calculation and prediction of the water quality index in relation to dissolved oxygen (DO), biochemical demand for oxygen (BOD), nitrates, fecal coliforms, potential for hydrogen ions (pH) and turbidity.